Economic agglomeration, economic growth and income inequality in regional economy - Imam Mukhlis; Isnawati Hidayah; Sariyani Sariyani (Economic Journal of Emerging Markets, 2018)
This study has the aims to analyse the relationship between economic agglomeration and economic growth to income inequality that occurs in regional development post-implementation of regional autonomy policy in East Java District / City of Indonesia in the year of 2011-2015. The method of analysis used is Panel Data with Random Effect Model. The result of the research concludes that economic agglomeration has significantly and positively affect on the level of income inequality that occurs in the regional economy. However, economic growth has no significant effect on income inequality in regional economy in East Java Province.